2014
DOI: 10.1002/asna.201312126
|View full text |Cite
|
Sign up to set email alerts
|

Search for circum‐planetary material and orbital period variations of short‐period Kepler exoplanet candidates

Abstract: A unique short-period (P = 0.65356(1) d) Mercury-size Kepler exoplanet candidate KIC012557548b has been discovered recently by Rappaport et al. (2012). This object is a transiting disintegrating exoplanet with a circum-planetary material-comet-like tail. Close-in exoplanets, like KIC012557548b, are subjected to the greatest planet-star interactions. This interaction may have various forms. In certain cases it may cause formation of the comet-like tail. Strong interaction with the host star, and/or presence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…With increasing distance from the planet, the dust grains speed up with respect to the planet. They also gradually sublimate due to the intense stellar irradiation, decreasing their 1 A search for more such objects amongst short-period Kepler exoplanet candidates did not find any additional ones (Garai et al 2014). …”
Section: Evaporating Rocky Exoplanetsmentioning
confidence: 99%
“…With increasing distance from the planet, the dust grains speed up with respect to the planet. They also gradually sublimate due to the intense stellar irradiation, decreasing their 1 A search for more such objects amongst short-period Kepler exoplanet candidates did not find any additional ones (Garai et al 2014). …”
Section: Evaporating Rocky Exoplanetsmentioning
confidence: 99%
“…The mass of the planet must be relatively small too, less than that of Mars, otherwise the material would not be able to escape from its deep gravitational well. This is supported by Garai et al (2014) who found no evidence for the dusty tails in other more massive close-in exoplanets observed by Kepler. The planet's tail is dominated by radiative and gravitational forces as well as an interplay between the grain condensation and evaporation.…”
Section: Introductionmentioning
confidence: 72%
“…These are 64 842 observations with an exposure time of about 30 min. Kepler observations were reduced in a similar manner to in Budaj (2013) and Garai et al (2014). Results of the period analysis of KOI 2700b.…”
Section: Observationsmentioning
confidence: 99%
“…Gravity of the more massive planets would provide too deep a potential barrier for the wind. Garai et al (2014) searched for comet-like tails in a sample of 20 close-in exoplanet candidates with a period similar to KIC 12557548b from the Kepler mission, however, none of the exoplanet candidates showed signs of a comet-like tail. This result is in agreement with the model proposed by Perez-Becker & Chiang (2013).…”
Section: Introductionmentioning
confidence: 99%